Cross-country differences in monetary policy execution and money market rates' volatility - Leonardo Bartolini; Alessandro Prati (Federal Reserve Bank of New York, 2003)
The volatility patterns of overnight interest rates differ across industrial countries in ways that existing models, designed to replicate the features of the U.S. federal funds market, cannot explain. This paper presents an equilibrium model of the overnight interbank market that matches these different patterns by incorporating differences in policy execution by the world's main central banks, including differences in central banks' management of marginal lending and deposit facilities in response to shocks. Our model is consistent with central banks' observed practice of rationing access to marginal facilities when the objective of stabilizing short-term interest rates conflicts with another high-frequency objective, such as the targeting of exchange rates.
Keywords: E43; E44; E52; 330; interbank market; interest volatility; central bank procedures; Zins; Geldmarkt; Geldpolitik; USA